EFFECTS OF FINANCIAL PERFORMANCE AND CORPORATE SOCIAL RESPONSIBILITY ON COMPANY VALUES: CASE OF BANKS LISTED ON THE INDONESIA STOCK EXCHANGE - Wahongan, Larey (Universitas Sam Ratulangi, 2019)
This study aims to analyze the effect of financial performance and corporate social responsibility (CSR) on the value of the company at banks listed on the Indonesia Stock Exchange for the period 2013-2017. The data used are secondary data, namely financial statements published on the Indonesia Stock Exchange's website during the period 2013-2017 which contain information about the ratio of banking financial performance (NPL, LDR, ROA, and CAR), Corporate Social Responsibility (CSR), and Value Companies with Tobin's Q method. This study consists of dependent variables and independent variables. The dependent variable is the value of the company, while the independent variable is financial performance and Corporate Social Responsibility (CSR).